2016
DOI: 10.1111/ctr.12671
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cytomegalovirus infection and disease pre‐ and post‐quantitative nucleic acid test standardization: does use of a more sensitive assay lead to longer treatment duration?

Abstract: Quantitative cytomegalovirus (CMV) nucleic acid testing (NAT) has been standardized using the World Health Organization (WHO) international calibration standard. A new FDA-approved WHO-calibrated assay (CA) was found to be more sensitive than a laboratory-developed test (LDT). We hypothesized that monitoring therapeutic response using a more sensitive assay may lead to longer antiviral therapy in solid organ and hematopoietic stem cell transplant patients with CMV infection. We reviewed transplant patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A recent study showed that using a more sensitive test does increase the time to reach an undetectable viral load; however, there was a trend towards shorter duration of therapy with the more sensitive assay. 55 Finally, treatment until viral load values are less than 137 IU/mL is predictive of a clinical response. 56 Though there is value to using highly sensitive assays, the practice of continuing therapy until successive viral load tests are undetectable may not be necessary when using such tests (ie, with highly sensitive assays, multiple very low results might be sufficient before stopping therapy).…”
Section: Posttransplant Testingmentioning
confidence: 99%
“…A recent study showed that using a more sensitive test does increase the time to reach an undetectable viral load; however, there was a trend towards shorter duration of therapy with the more sensitive assay. 55 Finally, treatment until viral load values are less than 137 IU/mL is predictive of a clinical response. 56 Though there is value to using highly sensitive assays, the practice of continuing therapy until successive viral load tests are undetectable may not be necessary when using such tests (ie, with highly sensitive assays, multiple very low results might be sufficient before stopping therapy).…”
Section: Posttransplant Testingmentioning
confidence: 99%
“…There was an initial concern that highly sensitive assays to manage the CMV infection resulted in prolonged treatments and unnecessary exposure to antiviral therapy 14 . However, a shorter time of treatment using standardized quantitative nucleic acid testing has been demonstrated in a previous study 17 , 18 . Additionally, as a direct consequence of a more prolonged treatment time with RT-PCR observed in our study, we expected that the rate of the retreating requirement was reduced, considering that reaching a virological suppression seems to be predictive of clinical response 17 .…”
Section: Discussionmentioning
confidence: 86%
“…Failure to eradicate plasma DNAemia at the end of treatment is the major significant predictor of virologic recurrence [ 126 ]. Two consecutive negative weekly CMV QNAT results were previously suggested (in studies that used less sensitive CMV QNAT assays), but a single negative test may suffice if a highly sensitive QNAT is performed [ 127 128 ]. The highly sensitive test in the aforementioned studies is the WHO-calibrated assay, which corresponds to the test used in hospitals in Korea.…”
Section: Preemptive Therapymentioning
confidence: 99%